Agricultural and food economics - Società italiana di economia agraria (Heidelberg, Germany : Springer-Verlag, GmbH, 2013)
"Agricultural and Food Economics (AFE) is an international peer-reviewed journal welcoming research articles from economists, scholars and researchers from all over the world to publish problem-oriented and high quality articles. AFE publishes only original articles from a wide variety of economic perspectives that address current and relevant issues related to the agricultural and food system. Published articles focus on applied analysis, the discussion of innovative results, and relevant policy and managerial implications."
Mode of access: World Wide Web.
Description based on: Volume 1, issue 1 (December 2013); title from homepage (publisher's Web site, viewed June 5, 2013).
Latest issue consulted: Volume 5, issue 1 (December 2017) (Springer Online, viewed June 14, 2017).
Keywords: Agriculture -- Economic aspects -- Periodicals; Produce trade -- Periodicals; Agriculture -- Economic aspects; Produce trade; Agricultural Economics; Electronic journals